(untitled) (Bangladesh Journal of Pharmacology, 2015)
The present study was performed to investigate the effect of retinoic acid fluoro chalcone (RAFC) on lipopolysaccharide (LPS) induced epithelial-mesenchymal transition (EMT) in PC3 and CWR22rv1 prostate cell lines. Lipo-polysaccharide (LPS) was used to induce epithelial-mesenchymal transition in prostate carcinoma cell lines. The results revealed that treatment of PC3 and CWR22rv1 cells with LPS resulted in significant changes in the morphological features of the EMT. The mesenchymal marker, vimentin expression was significantly increased whereas the expression level of E?cadherin was markedly decreased after the treatment. We also observed increased cell motility and higher level of transcription factor glioma?associated oncogene homolog 1 (Gli1) expression on LPS treatment. Treatment of prostate cells with RAFC reversed the morphological changes induced by LPS in prostate cells. RAFC also reduced the expression of EMT markers induced by LPS and suppressed the Gli1 expression. The resultant effect of these changes was the suppression of motility and invasiveness of the prostrate cells. Thus, RAFC exhibited anti?invasive effect on prostrate cells by inhibition of the EMT process via Hedgehog signaling pathway.